Information Disorder in the Chilean Constitutional Process: When Disinformation Originates with the Political Authorities Themselves - Charney, John (European journal on criminal policy and research, 2025)
In the context of an electoral campaign, the creation of an atmosphere of information disorder, as occurred during Chile’s constituent process, has multifaceted origins and a range of significant effects. It has become commonplace to attribute the global disinformation crisis to the role of social networks and their algorithms. However, this research focuses on a less-explored dimension: the disinformation generated by key political authorities and their role in fostering an environment of information disorder during a constitutional referendum. Based on the analysis of 3 real cases that occurred in 2022, we conclude that a political system committed to freedom of expression must also recognize limits of political authorities in a constituent process. Authorities who, during an electoral campaign, deliberately disseminate false messages that are certain to cause serious and immediate harm to the quality of information available to voters should face sanctions. Conversely, cases that do not meet these stringent criteria must remain unpunished to safeguard the space for political expression and debate.